Chemical Constituents from Himatanthus articulata - Barreto,Alaide de Sá (1998)
Chemical investigation of Himatanthus articulata (Vahl) Woodson led to the isolation of stigmasterol, sitosterol, cycloartenol, alpha-amyrin-3beta-O-cinnamoyl, beta-amyrin-3beta-O-cinnamoyl, lupeol-3beta-O-cinnamoyl, alpha-amirin-3beta-O-acetyl, beta-amirin-3beta-O-acetyl, lupeol-3beta-O-acetyl, ursolic acid, methylmyoinositol, 1beta-O-beta-D-glucopyranosylplumeric acid, plumeride-1beta-O-beta-D-glucopyranosyl, plumericin and isoplumericin. Spectroscopic analysis (IR, ¹H, 13C-NMR and MS) were used for the identification of these compounds and some derivatives.